2011
DOI: 10.1016/j.neuropharm.2011.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in oral nicotine intake in rats

Abstract: To study individual differences in nicotine preference and intake, male and female rats were given free access to a choice of oral nicotine (10 or 20 mg/L) or water for 24 hours/day for periods of at least six weeks, starting at adolescence or adulthood. A total of 341 rats, were used in four different experiments; weight, nicotine intake and total liquid consumption were recorded weekly. Results show that rats can discriminate nicotine from water, can regulate their intake, and that there are readily detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 68 publications
(100 reference statements)
4
61
4
Order By: Relevance
“…On the other hand, in the absence of nicotine (last 3 days of lactation), dams showed lower food intake with higher serum and milk leptin levels [78]. Our results differ from Nesil et al [74], which showed decreased body mass in female rats exposed to nicotine, but they were neither lactating nor pregnant. Also, there are differences between studies regarding the administration of nicotine.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, in the absence of nicotine (last 3 days of lactation), dams showed lower food intake with higher serum and milk leptin levels [78]. Our results differ from Nesil et al [74], which showed decreased body mass in female rats exposed to nicotine, but they were neither lactating nor pregnant. Also, there are differences between studies regarding the administration of nicotine.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, adolescent rodents display greater nicotine CPP as compared to adults across a wide range of experimental protocols, nicotine doses, and routes of administration [15][16][17][18][19][20][21][22]. Studies using IV and oral SA procedures have also shown that nicotine intake is higher in adolescent versus adult rats [23][24][25][26][27][28] and mice [29]. High doses of For a recent and comprehensive review of the physical and affective states produced by withdrawal in rodents and humans, the reader is referred to Hall et al [4] nicotine also produce aversive effects that are lower in adolescent versus adult rats [18,30].…”
Section: Tobacco Use In Vulnerable Populationsmentioning
confidence: 99%
“…Adult male and female Sprague Dawley rats (F 0 , n = 77), obtained from Ege University Animal Breeding Facility, were subjected to oral nicotine self-administration, as the founding population for the selective breeding of the high-NP and low-NP lines (Collins et al, 2012;Nesil et al, 2011). Rats were kept in same-sex groups with ad libitum access to food and water and were housed under standard laboratory conditions (20-22°C, 12-12 h light-dark cycle) when they were not being used for breeding or testing.…”
Section: Subjectsmentioning
confidence: 99%
“…When being tested for oral nicotine intake, each rat was housed individually. After the termination of oral nicotine self-administration, rats (n = 48) that consumed the highest and lowest nicotine were selected [high-NP Female (n = 14), Male (n = 13); low-NP Female (n = 7), Male (n = 14)], using the Ward Cluster Method (Nesil et al, 2011), as breeders for the next generation. In the following generations (F 1 -F 8 ) the highest nicotine consuming of the high-NP and the lowest of the low-NP were selected and outbred.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation